(untitled) (Zia e Tahqeeq, 2025)
Muslim jurists have been deriving [the answers of] every type of new issues on the basis of their own independent legal judgment, in the light of the permanent and eternal principles of the Quran and Sunnah. For such issues, i.e. the ones that are based on independent judgment, it is natural that there be difference of opinion between the jurists, and we find instances even during the period of the Prophet ﷺ and his companion. Now the question is, when the jurists dissent, which legal opinion should be taken to act upon it? This question definitely exists for the common person, but it is for the Muftis that it is most imperative today, that due to some change in circumstances, or to remove some difficulty, in the issues in which there are differences of opinion, which legal opinion should be chosen? In this regard, the jurists have written with much detail. Over here the only question that we are examining is that, if the majority of legists (fuqaha’) have consensus on a certain issue, and there are one or a few legists with a different opinion, can Muftis, in order to remove some difficulties or other juristic precepts issue a legal statement (fatwa) based on that singular opinion? What are the rules and regulations in this regard? What are the opinions of earlier and later scholars? In which scenarios is it permissible to issue legal statement (fatwa) based on singular opinion(s), and in which scenarios is it impermissible?